Minimising chemical crosslinking for stabilising collagen in acellular bovine pericardium: Mechanistic insights via structural characterisations. (15th October 2022) - Zhang, Yi; Zhang, Wenkai; Snow, Tim; Ju, Ying; Liu, Yang; Smith, Andrew J.; Prabakar, Sujay
Abstract: Chemically crosslinked acellular bovine pericardium (ABP) has been widely used in clinical practice as bioprostheses. To ensure its consistency and durability, crosslinkers are used in excess, with stability guided by indicators including the hydrothermal denaturation temperature, the enzymatic resistance and the degree of crosslinking. Yet, understanding of the intermolecular structure in collagen fibrils which imparts the intrinsic stability of the ABPs is lacking, and the discrepancies in the stability criteria in varied conditions are poorly explained. In this study, synchrotron small-angle X-ray scattering (SAXS) in combination with thermal and colorimetric methods are employed to investigate the changes in the structure and the stability of ABPs during crosslinking using glutaraldehyde (GA) or 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) at different concentrations. Based on the findings, a mechanism is proposed to explicate the crosslinking effects on collagen structure and the relationship between the structure and each stability indicator. At low crosslinker concentrations, the telopeptidyl-helical linkages are preferred, which cause rearrangements in the intermolecular structure of collagen, and efficiently contribute to its stabilities. Excess crosslinking is revealed by a revert trend in structural changes and the plateauing of the stabilities, assigning to the helical-helical linkages and monovalent bindings. The former would improve thermal stability but not collagenase resistance, whereas the latter have negligible effects. Overall, this study provides a mechanistic understanding of the chemical crosslinking of ABPs, which will contribute to the future development of more efficient and economically viable strategies to produce bioprostheses. Statement of significance: Chemical crosslinking imparts suitable properties to acellular bovine pericardium (ABP) for clinical applications, yet the understanding is lacking on the structure-stability relationship especially under different crosslinking conditions. Structural evidence in this study differentiates the binding sites during crosslinking in collagen fibrils at different crosslinker concentrations, highlighting the excess usage in the conventional crosslinking treatments. The mechanism based on the structure of collagen also successfully explains the dissimilarity in hydrothermal and enzymatic stabilities with varied crosslinking conditions. Future researches focusing on developing biomaterials via chemical crosslinking of ABPs would benefit from this study, for its contribution to the better understanding of the relationship of collagen structure and functions. Graphical abstract: Image, graphical abstract